Nutritional screening among nursing home residents at rumah Seri Kenangan, Kelantan - Fazilah, Mohd Noh (Universiti Sains Malaysia, 2009)
Most research found that malnutrition among nursing home was high. Malnutrition was a public issue which everyone was too worried because it can cause the health condition of elderly become worst. The purposes of this study were to identify the nutritional status and prevalence of high risk of malnutrition among nursing home residents. On the other hand, the purpose of this study to determine the association of nutritional status and socioeconomic status, functional status, weight loss, mid upper arm circumference and calf circumference. This cross sectional study done in Rumah Seri Kenangan (RSK), Kelantan involved 68 of respondents who were 60 years of age and above and full fill the inclusion criteria that had determined before. This study use questionnaire which consists of three parts which personal and social data, anthropometry measurements and questions of MRST-H. The results showed that, 14.7% of respondents were undeiWeight (BMI < 18.5 kg/m2 ), 58.8% of respondents were normal, 19.1% of respondents were oveiWeight and 7.4% of respondents were obesity. 11.8% of respondents were high risk for malnutrition which 4 respondents were male and 4 respondents were female. There were significant association between nutritional status and weight loss (p<0.001 }, mid upper arm circumference (MUAC) (p=0.046} and calf circumference (CC) (p<0.001 ). There was no significant association between nutritional status and functional status (p=0.118). As a conclusion, this study found that more elderly in RSK, Kelantan were underweight and high risk for malnutrition. The nutritional status had significant association with weight loss, MUAC and CC but not significant with functional status.